UV-vis Investigation of β-Carotene in Presence of AOT/n-Heptane, Cyclohexane, Tetrahydrofuran/Water System - Bhattarai, Ajaya; Wilczura-Wachnik, Hanna (Journal of Applied Solution Chemistry and Modeling, 2013)
The precise measurements of β-carotene absorbance in presence of AOT/solvent/water systems at 25oC by UV-vis technique are reported. The solvents selected were: n-heptane, cyclohexane, and tetrahydrofuran. The concentrations of AOT [Aerosol-OT (sodium bis(2-ethylhexyl) sulfosuccinate)] were varied from 0.01 to 0.2mol/kg.β-carotene concentration in quvette during UV-vis spectrum registration was not the same in each solvents because of different absorption intensity depending on the solvent. Water concentration in the studied systems was defined by R parameter according to relation: R=[H2O]/[AOT] and was equal 0; 5; 10 both in n-heptane and cyclohexane, and 0; 10 and 20 in tetrahydrofuran. Obtained results showed a noticeable decreasing of β-carotene absorbance as a function of AOT concentration. There is evidenced red shift of β-carotene absorbance depending on the solvent in the following order: tetrahydrofuran >cyclohexane>n-heptane. Presented results show that β-carotene absorbance decreased with water concentration in the system. It had been happened because the water molecules located in the core of micelles make its curvature bigger and the hydrocarbon chains forming palisade layer in AOT reversed micelles get more space. As a consequence β-carotene molecules penetrated this layer dipper comparing to systems without water. <!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–>